Mechanical and physical properties of carbon nano tubes with kevlar fiber reinforced with polyester resin - Atallah, Marwa Subhi (Iraqi Journal of Physics, 2019)
In this research study Hardness (shore D), Water absorption, Flexural, Impact Test, and Fracture Toughness of polymer nano composites. The polymer nano composites based on unsaturated polyester resin reinforced with Kevlar fibers (K.F). The samples are attended by hand lay – up method according to (Rule mixture) for various volume fractions of unsaturated polyester resin, fiber and carbon nanotube. The polyester resin was matrix strengthened with 3% volume fraction from Kevlar fiber and (0.5%, 1%, 1.5%, 2%) volume fractions of carbon nanotube. The water absorption, hardness (shore D), flexural test, impact test and toughness fracture properties were studied. Results showed that the water absorption increase with volume fraction increase of fiber with Carbon Nanotube, the sample (polyester+3%K.F+0.5% CNTs) has lower water absorption than other samples. The hardness (shore D), flexural test, impact test and toughness fracture for the sample (polyester+3%C.F+0.5% CNTs) has higher value for Nano- composites.